Comprehensive analysis of proline metabolizing genes reveals their functional diversification and abiotic stress response in Solanum lycopersicum - Md. Afser Rabbi; Md. Muluk Hossain; Md. Rihan Kabir Shuvo; Asifur Rob Bhuya; Ajit Ghosh (PLoS ONE, 2025)
Proline plays a crucial role in plant stress responses. Proline metabolizing genes (PMGs) are a group of enzymes involved in its catabolism in mitochondria and the biosynthesis in the chloroplast and cytoplasm. A total of 21 PMGs were identified in Solanum lycopersicum . Among them, 2 gene pairs were identified as tandemly duplicated, and 6 gene pairs were segmentally duplicated. Phylogenetic analysis revealed distinct gene clusters, suggesting functional diversification. Gene structure analysis provided insights into the arrangement of coding and non-coding regions, while domain analysis highlighted conserved sequences for functional predictions and evolutionary conservation. Microarray expression data of the identified genes revealed that SlOAT8 exhibited maximum expression in different anatomical tissues, particularly in ovules, and SlOAT9 showed maximum response at developmental stages associated with shoot growth. Under stress conditions, SlOAT8 and SlP5CS1 were upregulated in exposure to drought stress but downregulated in response to heat and salt stress. Meanwhile, SlOAT4 was strongly expressed only in roots during salt stress. The qRT-PCR analysis demonstrated significant upregulation of SlOAT8 , SlP5CDH2 , and SlP5CR alongside a significant downregulation of SlP5CS1 under abiotic stress conditions. Furthermore, biochemical assay indicates the accumulation of proline and H 2 O 2 under stressed conditions. These findings provide an extensive study on the PMGs, which will help in the development of a stress-resilient tomato plant in further.